Fronto-Subcortical Circuits for Cognition and Motivation: Dissociated Recovery in a Case of Loss of Psychic Self-Activation - Riveros, Rodrigo; Bakchine, Serge; Pillon, Bernard; Poupon, Fabrice; Miranda, Marcelo; Slachevsky, Andrea (Frontiers in Psychology, 2019)
In humans and non-humans primates, extensive evidence supports the existence of subcortico-cortical circuits for cognition and behavior. Lesions studies are critical to understand the clinical significance of these functionally segregated circuits. Mapping these circuits from lesion studies is difficult given the heterogeneous etiology of the lesions, the lack of long-term and systematic testing of cognitive and behavioral disturbances, as well as the scarcity of neuroimaging data for identifying the precise location and extent of subcortical lesions. Here, we report the long-term follow-up study of a patient who developed a loss of psychic self-activation associated to a dysexecutive syndrome following resuscitation from cardiac arrest. Neuroimaging revealed extensive bilateral lesions in the putamen, with a relative spare of the caudate, and exhibiting a dorsoventral gradient that was predominantly rostrally to the anterior commissure and spared most of the ventral striatum. In comprehensive neuropsychological and neuropsychiatric assessments, we observed dissociation between the improvement of the self-activation deficits and the stability of the dysexecutive syndrome. The pattern of recovery after this lesion lends support to current models proposing the existence of two main subcortico-cortical circuits: a dorsal circuit, mostly mediating cognitive processes, and a ventral circuit, implicated in motivation.